Ecowomanism, religion, and ecology - Harris, Melanie L. (Brill, 2017)
Front Matter /Melanie L. Harris -- Introduction /Melanie L. Harris -- Ecowomanism /Melanie L. Harris -- Nankani Women’s Spirituality and Ecology /Rose Mary Amenga-Etego -- Turning Weapons into Flowers /Xiumei Pu -- Seeds of Light, Flowers of Power, Fruits of Change /Layli Maparyan -- Between Dishwater and the River /Sofía Betancourt -- Afro-Brazilian Religion, Resistance and Environmental Ethics /Valdina Oliveira Pinto and Rachel E. Harding -- Earth Hope /Mercy Oduyoye -- Index /Melanie L. Harris.